Comparison of Honey Versus Normal Saline in the Management of Post-Operative Infected Wounds in Pediatric Urology Patients - Majid Khan Kakakhel, Muhammad Kamran Khan, Sami Ullah, Muhammad Asif, Abdullah Shaikh, Abdullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Honey exhibits a variety of bacteriostatic and bactericidal factors. Due to its variety of antimicrobial and wound healing properties, honey is an effective remedy in wound infections even caused by microorganisms resistant to antibiotics. Nevertheless, there are many known benefits of normal saline soaked gauze dressing as well such as its osmotic properties, cost-effectiveness, and easy availability with no side effects. It is believed that honey as well as normal saline could be used in the management of infected and non-healing wounds and ulcers, pressure wounds, burns, boils, pilonidal sinuses, diabetic and venous ulcers and even malignant wounds with respect to wound size and cleanliness. Purpose of Study: The purpose of this study is to compare the effect of topical honey versus normal saline soaked dressing application in the management of cosmetically improved postoperative infected wounds in pediatric urology patients. Material and Methods: This Randomized Controlled trial was conducted at the Institute of Kidney Diseases (IKD), Hayat Abad Medical Complex (HMC), Peshawar commencing from January 2019 till December 2019 i.e., over a period of one year. Pediatric patients with postoperative wound infections with positive wound cultures were included in the study. The patients were divided into two groups. In group A normal saline soaked dressing was applied and in group B honey was applied three times a day each. Results: A sample size of 60 patients was taken with males 35(58.3%) and females 25(41.7%). Mean age was 5 years with standard deviation of 2.15 with minimum age 1 year and maximum age 10 years. The bacteria on wound culture came out to be Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli in descending order. Patients were divided into two groups. Group A included 30 patients with normal saline soaked dressing application to the wound while Group B included 30 patients with honey application to the infected wound. Both groups were compared in terms of scar improvement and results were found statistically significant 0.028 in group B (Honey). Conclusion: Honey can be used safely and effectively for the management of postoperative surgical site infections in pediatric urology patients as compared to normal saline soaked dressings. Keywords: Honey, postoperative infected wound, pediatric patients